Az-Zaitun Sharia People's Market as a Grassroots Model of Halal Education in Indonesia: A Systems-Based Maqashid Perspective - Miswanto, Agus; Siti Fatimah; Anwar, Syamsul (Jurnal Tarbiyatuna, 2026)
This study examines the Az-Zaitun Sharia People's Market in Surabaya as a grassroots model of halal education through the lens of Jasser Auda's systems-based maqashid framework. Using a qualitative socio-legal case study, data were collected from field observations, an interview with the market manager, previous empirical studies, and halal regulatory documents. The findings indicate that the market promotes halal education by integrating halal commodities, honest transactions, accurate weighing, cleanliness, smoke-free norms, and ethical pricing into everyday trading practices. However, several challenges remain, including selective halal certification, inconsistent sanitation, limited compliance with smoke-free regulations, inadequate metrology supervision, and weak institutional collaboration with halal authorities. The study concludes that community-based halal education is most effective when local cultural practices are integrated with formal halal governance, thereby strengthening participatory halal assurance and fostering sustainable Islamic educational values within public economic spaces.